CONTEMPORARY STRATEGIES FOR CONTROLLING MYOPIA PROGRESSION: A NARRATIVE REVIEW - J.E.; MOYEGBONE; E.O EMUROTU; E.E. ORONSAYE; P. ONYEMA; M.I. NKOLLO (African Journal of Health, Safety and Environment, 2026)
Myopia is one of the refractive errors and the most common global health issue amongst young people. Progressive myopia results in the elongation of the eyeball, and puts patients at risk of vision-altering conditions such as cataracts and glaucoma. Traditional method of mitigating myopia was simply correcting the refractive error using single-vision lenses, and this method is largely replaced by myopia control techniques. The goal of these interventions is to slow the progression of myopia by limiting ocular growth. This review addresses newer control methods such as orthokeratology, myopia control contact lenses, myopia control spectacles, therapeutic low-dose atropine, and increased time outside. The review is based on publications found in various peer-reviewed and reputable medical databases. Traditional literature has highlighted the benefits of each technique. Current literature also addresses how combined methods of myopia control achieves superior results to single methods. Also, the use of low-level red light therapy and artificial intelligence to assess and control myopia shows great potential in improving myopia control. This review also addresses the importance of tailoring myopia control techniques to the individual and to their specific socioeconomic situations. Adaptability, especially in low resource environments, is the hallmark of modern myopia control.